The Influence of Taxonomy and Environment on Leaf Trait Variation Along Tropical Abiotic Gradients - Oliveras Menor, I.; Bentley, L.; Fyllas, N.M.; Gvozdevaite, A.; Shenkin, A.F.; Peprah, T.; Morandi, P.; Peixoto, K.S.; Boakye, M.; Adu-Bredu, S.; Schwantes Marimon, B.; Marimon-Júnior, B.H.; et al. (Frontiers Media, 2020)
Deconstructing functional trait variation and co-variation across a wide range of environmental conditions should increase the mechanistic understanding of community assembly processes and improve current parameterization of dynamic vegetation models. Here, we present a study that deconstructs leaf trait variation and co-variation to iithin-species, taxonomic-interspecific, and plot-environment components comparing three tropical environmental gradients in Peru, Brazil and Ghana. We measured photosynthetic, chemical and structural leaf traits using a standardized sampling protocol, totalling more than 1,000 individuals belonging to 367 species sampled. Variation associated with the whole interspecific taxonomic component (species+genus+family) for most traits was relatively consistent across environmental gradients, but intra-specificwithin-species variation and the plot-environment variation was strongly dependent on the environmental gradient. Trait-trait co-variation was also strongly linked to the environmental gradient where the traits were measured, although some traits had consistent co-variation components irrespective of environmental gradient. Our results demonstrate that filtering along gradients is mostly expressed through trait intra- and interspecifictaxonomic variation, but that trait co-variation is strongly dependent on the local environment, and thus global trait co-variation relationships might not always apply at smaller scales and may quickly change under future climate scenarios.
Keywords: Trait; Interspecific competition; Biology; Variation (astronomy); Abiotic component; Environmental gradient; Environmental change; Ecology; Gradient analysis; Ordination; Climate change; Habitat; https://purl.org/pe-repo/ocde/ford#1.06.13